Micromagnetic Modeling on Magnetisation Dynamics with Lossy Magnetic Material in Thin Film Heads by FDTD Calculations - Recio, Gustavo; Est´ ebanez, Cesar (Applied Computational Electromagnetics Society Journal (ACES), 2021)
An extension to the standard FDTD formulation aimed at modelling the micromagnetics of materials together with the solution of Maxwell’s equations is presented in this paper. Numerical computations using actual thin film head geometries were carried out with the purpose of validating the method. The analysis of results revealed the importance of the method for modelling electromagnetic interaction with lossy magnetic material in the presence of current and magnetic sources.